2020
DOI: 10.5387/fms.2019-31
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation arising from mature cystic teratoma of the ovary presenting as ovarian torsion: a case report and literature review

Abstract: Objective : Ovarian torsion is an acute gynecological condition. Torsion is more likely to occur with benign rather than malignant tumors. Mature cystic teratoma of the ovary (MCTO) is frequent in women of reproductive age ; however, the incidence of malignant transformation is approximately 2%. We report a case of malignant transformation of MCTO presenting as ovarian tumor torsion. Case report : A 51 -yearold premenopausal woman was diagnosed with mature cystic teratoma in the left ovary 7 years ago. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…8 However, a low level of SCC antigen does not rule out carcinoma. 6,15 In this case, CA 125 was the only tumor marker being evaluated, and it was increased. Unfortunately, in our case, due to the technical impossibility of routine clinical practice, SCC antigen was not measured.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…8 However, a low level of SCC antigen does not rule out carcinoma. 6,15 In this case, CA 125 was the only tumor marker being evaluated, and it was increased. Unfortunately, in our case, due to the technical impossibility of routine clinical practice, SCC antigen was not measured.…”
Section: Discussionmentioning
confidence: 82%
“…Bloating, loss of appetite, and weight loss are other symptoms reported previously. 6,8 MT-MCTO tumors are typically located in one ovary but can involve both ovaries in 10%-17% of the cases. The tumor mass size is usually large (10-20 cm in diameter), 8 and larger than benign tumors, possibly due to the presence of additional areas of necrosis or hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative differential diagnosis between pelvic inflammatory disease and adnexal torsion with mature cystic ovarian teratoma in our patient was challenging. Rare cases of malignant transformation of mature cystic ovarian teratoma have been described in the literature, in which abdominal pain and vomiting were incorrectly attributed to adnexal torsion [ 13 , 14 ]. In addition, in rare isolated cases, mature cystic teratoma may coexist with ovarian lymphangioma or plasmablastic lymphoma with all the difficulties related to the correct diagnosis [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of malignant transformation varies from case report to case series, accounting for 1–3% of all the MCT cases. [ 3 , 8 ] Over a period of 40 years, only 2 case series have reported that the frequency of MT-MCT was as high as 6.67% [ 9 ] and 5%, [ 10 ] respectively. In our study, the incidence was 2.4%, which is consistent with the reported literature.…”
Section: Discussionmentioning
confidence: 99%